Attittude As A Factor Of Lifestyle Formation In people With Special Needs - Kreidun, Nadia; Polivanova, Olena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article deals with the problem of an attitude as a factor of lifestyle formation in people with special needs. The results obtained allow us to ascertain the presence of psychological mismatch between self-concept of a person with special needs, and his interpretation of the requirement imposed on him by society. As a rule, it is more fied in women: expectations of society women turning into their own regulations. Men have attitude toward self related to values, aimed at preserving their own individuality: primarily health and focus on the immediate satisfaction of vital needs. Identifid gender differences in relation to self, can act as one of the internal factors of the lifestyle in people with special needs.